2008
DOI: 10.1111/j.1528-1167.2008.01603.x
|View full text |Cite
|
Sign up to set email alerts
|

Decreased hippocampal volume on MRI is associated with increased extracellular glutamate in epilepsy patients

Abstract: SUMMARYPurpose: Temporal lobe epilepsy (TLE) is associated with smaller hippocampal volume and with elevated extracellular (EC) glutamate levels. We investigated the relationship between the hippocampal volume and glutamate in refractory TLE patients. Methods: We used quantitative MRI volumetrics to measure the hippocampal volume and zero-flow microdialysis to measure the interictal glutamate, glutamine, and GABA levels in the epileptogenic hippocampus of 17 patients with medicationresistant epilepsy undergoin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
71
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(80 citation statements)
references
References 60 publications
9
71
0
Order By: Relevance
“…Our data are supported by previous report 21 , which demonstrated increased extracellular glutamate levels (increased release), using microdialysis probes in humans with TLE. A deficiency in glutamine synthesis in astrocytes, found by several authors 22 , can also explain the high levels of glutamate in extracellular space, suggesting increased release of this amino acid.…”
Section: Discussionsupporting
confidence: 82%
“…Our data are supported by previous report 21 , which demonstrated increased extracellular glutamate levels (increased release), using microdialysis probes in humans with TLE. A deficiency in glutamine synthesis in astrocytes, found by several authors 22 , can also explain the high levels of glutamate in extracellular space, suggesting increased release of this amino acid.…”
Section: Discussionsupporting
confidence: 82%
“…41 This caveat appears particularly relevant for cross-sectional studies. In 18 of the latter (47.4%), 14,16,[20][21][22]24,30,[33][34][35][36][37][38]40,42,[50][51][52] no statistical approaches were implemented to correct for the effects of age. Although the remaining studies addressed aging, no consistent method was chosen: 3 reported no significant effects of age on morphometric measures in controls, 15,32,48 3 found no effect of age or no effect of age at epilepsy onset in patients, 19,29,53 2 corrected for age at onset, 18,28 5 corrected for age in patients, 17,26,47,49,54 4 utilized MRI measures adjusted for age 13,31,39,46 (based on regression models derived from controls), 1 calculated epilepsy duration/age ratios, 23 2 statistically compared chronological age effects between patients and controls.…”
Section: Resultsmentioning
confidence: 99%
“…43 The increased interictal basal extracellular glutamate levels negatively correlate with hippocampal volume being significantly increased in the atrophic 43 hippocampus compared to nonatrophic ones. 71 The hippocampal volume negatively correlates with seizure frequency. 71 Magnetic resonance spectroscopic measurements show that cellular glutamate levels are also lower in the atrophic (sclerotic) hippocampus compared to the nonatrophic one.…”
Section: Glutamate Glutamine Cyclingmentioning
confidence: 99%
“…71 The hippocampal volume negatively correlates with seizure frequency. 71 Magnetic resonance spectroscopic measurements show that cellular glutamate levels are also lower in the atrophic (sclerotic) hippocampus compared to the nonatrophic one. 72 However, tissue glutamate levels measured by proton magnetic resonance spectroscopy of perchloric acid tissue extracts show that the cellular glutamate content is increased above normal levels in the epileptogenic human hippocampus.…”
Section: Glutamate Glutamine Cyclingmentioning
confidence: 99%